2020
DOI: 10.3390/s20215989
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Physical Rehabilitation Using Serious Videogames and Motion Capture Systems: A Systematic Review

Abstract: The use of videogames and motion capture systems in rehabilitation contributes to the recovery of the patient. This systematic review aimed to explore the works related to these technologies. The PRISMA method (Preferred Reporting Items for Systematic reviews and Meta-Analyses) was used to search the databases Scopus, PubMed, IEEE Xplore, and Web of Science, taking into consideration four aspects: physical rehabilitation, the use of videogames, motion capture technologies, and upper limb rehabilitation. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 56 publications
0
28
0
2
Order By: Relevance
“…Finally, further exploration is recommended in approaches related to neuromotor rehabilitation and EEG signal acquisition systems, since while some advances address the topic [ 22 , 27 , 33 , 34 , 41 , 46 ], exoskeletons with application in motor rehabilitation are more common. It is highlighted that the addition of new virtual systems can increase neuronal plasticity in a controlled rehabilitation environment, so it is necessary to consider extending the scope to systems outside the robotic exoskeletons [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, further exploration is recommended in approaches related to neuromotor rehabilitation and EEG signal acquisition systems, since while some advances address the topic [ 22 , 27 , 33 , 34 , 41 , 46 ], exoskeletons with application in motor rehabilitation are more common. It is highlighted that the addition of new virtual systems can increase neuronal plasticity in a controlled rehabilitation environment, so it is necessary to consider extending the scope to systems outside the robotic exoskeletons [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aşkın et al [32] used VR technology based on somatosensory sensors to assist stroke patients with upper limb motor function rehabilitation. The research by Aldana et al [33] has shown that the use of video games and motion capture systems in upper limb rehabilitation can contribute to patient rehabilitation. With the rapid development of artificial intelligence and Internet technology, the research in the field of intelligent rehabilitation has increased rapidly.…”
Section: Related Workmentioning
confidence: 99%
“…The motion capture systems used vary, depending on multiple forms of demand, for example we have Fig. 1 [11] and regarding, of course the body area treated, the distribution chart below can express the demand resultsstating this as leverage for sustaining the idea that no work of motion capture, treatment, or reproduction of motion capture and treatment technology is to be researched without demand, implying purpose. Fig.…”
Section: State Of the Artmentioning
confidence: 99%